2019
DOI: 10.1002/srin.201900059
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Microstructure on the Bendability of Direct Quenched Wear Resistant Steel

Abstract: The influence of chemical composition and processing parameters on the microstructure and bendability of three thermomechanically rolled and directquenched wear resistant steel plates is studied. Overall, the bendability of the steels is good, but there are exceptions that are given special attention. The prior austenite condition and final microstructure is evaluated with respect to subsurface hardness and bendability. The possible effect of inclusions on bendability is taken into account. Away from the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…However, this parameter was very small in the transverse direction in comparison with longitudinal one, a fact that can be caused by the strong crystallographic texture that steel acquired during the hot rolling. This result is consistent with the one published by Kaijalainen et al [13] since they argued that bendability in the transverse direction in a conventional steel was affected by the presence of martensite-austenite plates aligned in the rolling direction and the predominantly shear texture {112}<111> component. Regarding the CBA of the IA samples, it was observed that the highest value was achieved in the longitudinal direction (103.1°), however in this case the difference between longitudinal and transverse was only 8°, which indicates that IA treatment improved markedly the bending properties of the steel sheet.…”
Section: Bending Testingsupporting
confidence: 92%
“…However, this parameter was very small in the transverse direction in comparison with longitudinal one, a fact that can be caused by the strong crystallographic texture that steel acquired during the hot rolling. This result is consistent with the one published by Kaijalainen et al [13] since they argued that bendability in the transverse direction in a conventional steel was affected by the presence of martensite-austenite plates aligned in the rolling direction and the predominantly shear texture {112}<111> component. Regarding the CBA of the IA samples, it was observed that the highest value was achieved in the longitudinal direction (103.1°), however in this case the difference between longitudinal and transverse was only 8°, which indicates that IA treatment improved markedly the bending properties of the steel sheet.…”
Section: Bending Testingsupporting
confidence: 92%
“…Compared with high manganese steel and high chromium cast iron, as a widely used low alloy high strength wear-resistant steel, NM500 has the advantages of low cost and easy processing [3][4][5][6]. It corresponds to the AR500 grade under the ASTM standard.…”
Section: Introductionmentioning
confidence: 99%
“…The bending performance can be improved by lowering the hardness and improving the uniformity of the microstructure at the surface and subsurface layer, which increase the uniformity of the strain distribution along the bending axis [6]. During the bending process, the large size brittle martensite-austenite (MA) constituents or inclusions at the sub-surface layer are broken or separated from the matrix, easily giving rise to the cavities, thus forming the bending cracks [7].…”
Section: Introductionmentioning
confidence: 99%